Mesoporous carbon nanotube aerogel-sulfur cathodes: A strategy to achieve ultrahigh areal capacity for lithium-sulfur batteries via capillary action. (30th September 2020) - Fang, Zhenhan; Luo, Yufeng; Wu, Hengcai; Yan, Lingjia; Zhao, Fei; Li, Qunqing; Fan, Shoushan; Wang, Jiaping
Abstract: A strategy to produce sulfur (S) cathodes with ultrahigh areal capacity for lithium-sulfur (Li–S) batteries is proposed. Porous carbon nanotube (CNT) aerogel@Li2 S8 cathodes are obtained by dropping Li2 S8 solution into the CNT aerogels that are prepared through a freeze-drying method. The three-dimensional (3D) porous structure of the CNT aerogel provides a complete electron transport network and rapid ion transport channels. Moreover, the rich mesoporous structure has an extreme capillary action on the electrolyte. Numerical simulation shows that in a surprisingly short time (2 μs), the electrolyte can be absorbed into the mesopores by capillary action and reach a stable state, limiting the "shuttle effect" of polysulfides. Based on these unique characteristics, the CNT aerogel@Li2 S8 cathode exhibits excellent electrochemical performance. With an extremely high areal S loading of 20 mg cm −2, the cathode shows an ultrahigh areal specific capacity of 22.9 mAh cm −2 . For the pouch cell with an areal S loading of 10 mg cm −2 and a low electrolyte/sulfur (E/S) ratio of 7.8 μL mg −1, the areal specific capacity reaches a high value of 10.4 mAh cm −2 . Graphical abstract: Image 1